Twist within a somersault - Mikl, J.; Rye, D. C. (Human Movement Science, 2016)
The twisting somersault is a key skill in diving and gymnastics. The components of twist and somersault are defined with respect to anatomical axes, and combinations of multiples of half rotations of twist and somersault define specific twisting somersault skills. To achieve a twisting somersault skill twist must be continuous; otherwise oscillations in twist while somersaulting may be observed. The posture-dependent inertial properties of the athlete and the initial conditions determine if continuous or oscillating twist is observed. The paper derives equations for the amount of somersault required per half twist, or per twist oscillation, without making assumptions about the relative magnitudes of the moments of inertia. From these equations the skills achievable may be determined. The error associated with the common assumption that the medial and transverse principal moments of inertia are equal is explored. It is concluded that the error grows as the number of twists per somersault decreases, when the medial and transverse moments of inertia diverge, and when the longitudinal moment of inertia approaches either the medial or transverse moment of inertia. Inertial property data for an example athlete are used to illustrate the various rotational states that can occur. - Derived equations for twist completed as a function of somersault: defining skills. - No assumptions regarding the relative magnitude of the principal moments of inertia. - No restrictions on initial orientation with respect to the angular momentum vector. - Validity of assuming equality of medial and transverse moments of inertia assessed. - One example athlete`s inertial properties used to illustrate.